Development of a Sustainable Fashion Mobile Application Prototype Using Rule-Based Filtering Approach - Nila Natalia; Zahra Ramadhani Putri; Irfan Nafis Sjamsuddin (Journal of Applied Information System and Informatic (JAISI), 2026)
Abstract— Rapid growth in the fast fashion industry has increased consumer behavior, especially among college students. This growth led to a surge in textile waste. This study aims to design and develop a mobile application prototype named "ReHue" as a digital solution. The app promotes sustainable fashion through a smart wardrobe management and donation system. This study uses a quantitative, applied approach. It focuses on UI/UX design in Figma and prototyping with React Native. Materials analyzed include literature on the circular economy, rule-based filtering algorithms, and textile waste management. The proposed system applies a rule-based filtering approach. It gives personalized clothing recommendations based on real-time weather and the user's color profile. The system uses a threshold-based tracking mechanism. It triggers notifications when clothing has been unworn for more than 210 days, encouraging users to donate through a gamified feature. Experimental results from logic scenario testing show the system can execute recommendation rules and trigger alerts as intended. By offering monetary rewards in the donation flow, the system incentivizes users to reduce textile waste. This research suggests ReHue can help transform impulse-buying habits into ecological actions. Future research should integrate real-time API connectivity and advanced machine learning models to improve recommendations and user engagement across wider reverse logistics networks. Keywords— Sustainable fashion; Smart wardrobe; Rule-based filtering; Mobile application; Textile waste